PENDIDIKAN KEJUJURAN DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM DI SMK KABUPATEN LABUHANBATU SUMATERA UTARA - Bukhari Is; Ahmad Tafsir; Hendri Tanjung (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2017)
This study used a qualitative phenomenological approach, thus, the researcher is the key instrument. Data collection is using the technique of interview, observation, open questionnaire and Focus Group Discussion (FGD). The formulation of the problem is how the concept of honesty education in addressing the low of students and alumnus honesty at vocational high schoolKeywords: Education, Honesty, Curriculum, Vocational Education.